2013
DOI: 10.1097/sih.0b013e31828e716d
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Intervention With Manikin-Based Objective Metrics Improves CPR Instructor Chest Compression Performance Skills Without Improvement in Chest Compression Assessment Skills

Abstract: Real-time compression feedback during simulation improved CPR-I/C's chest compression performance skills without comparable improvement in chest compression assessment skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…Adequacy of chest compression rate or depth in a given scenario was defined as either an average within the specified parameters or meeting the specified parameter for >80% of the compressions analysed. 17 The >80% adequate analysis was undertaken to confirm that the analysis using averages was not being adversely affected by outliers. 15 Chest compression fraction was calculated by the Laerdal SimMan 3G as amount of time compressions that were performed divided by the amount of time that compressions were indicated and reported as a percentage.…”
Section: Discussionmentioning
confidence: 99%
“…Adequacy of chest compression rate or depth in a given scenario was defined as either an average within the specified parameters or meeting the specified parameter for >80% of the compressions analysed. 17 The >80% adequate analysis was undertaken to confirm that the analysis using averages was not being adversely affected by outliers. 15 Chest compression fraction was calculated by the Laerdal SimMan 3G as amount of time compressions that were performed divided by the amount of time that compressions were indicated and reported as a percentage.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the use of real-time feedback devices, experienced CPR instructors have difficulty in their accuracy of visual assessment of CPR quality. 19 Further, in a study conducted after real CPA events, team leaders were unable to recall significant CPR mistakes made during the CPA resuscitation. 18 Our results confirm what previous studies have shown, but are unique in that we specifically examined the accuracy of real-time assessment on specific CPR metrics, as opposed to previous studies 17, 18 that have surveyed providers following arrests.…”
Section: Discussionmentioning
confidence: 98%
“…18 Furthermore, with handson feedback of CPR performance, visual assessment of CPR quality does not improve even in skilled CPR instructors. 19 No studies to date have examined the accuracy of visual assessment of CPR quality. Additionally, the optimal positioning of the observer relative to the patient for accurate assessment has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Novice instructors are more likely to make a fail decision than trained assessors in learner assessment (Thorne, Jones, Harvey, Hulme, & Owen, 2013). Similarly, even experienced BLS instructors show low accuracy of visual assessment for CPR quality via video review (Al- Rasheed et al, 2013). The overall accuracy of visual assessment of CPR quality has been reported to be 65.6% (Jones, Lin, Nettel-Aguirre, Gilfoyle, & Cheng, 2015).…”
Section: Competence Of Basic Life Support Instructorsmentioning
confidence: 99%
“…In resuscitation training, the competence of the instructor is important to guarantee optimal CPR performance of health-care professionals by standardized education (Al-Rasheed et al, 2013;Morley et al, 2015). Regarding the effect of structured education on CPR instructors, BLS instructors who have participated in the assessment training program show increased post-test confidence in assessing candidates compared to pre-test (Thorne, Jones, Coffin, Hulme, & Owen, 2015).…”
Section: Competence Of Basic Life Support Instructorsmentioning
confidence: 99%